Hard and soft tissue shape variation and changes in Class II division 1 malocclusion during orthodontic treatment: a geometric morphometric analysis - Chin Sin Chu; Murshida Marizan Nor; Alizae Marny Mohamed; Helmi Mohd Hadi Pritam (BMC, 2023)
Abstract Background This study aims to determine the hard and soft tissue shape variation and its changes in Class II division 1 malocclusion before and after orthodontic treatment using Geometric Morphometric Analysis. Methods This retrospective study included 141 pre-treatment and near-end treatment lateral cephalometric radiographs of Class II division 1 malocclusion patients aged 16-40 years with a skeletal II pattern (ANB > 4o). 32 landmarks in Cartesian coordinates were created and identified using MorphoJ software to establish a shape analysis. Results The vertical dimensions (hypodivergent to hyperdivergent facial profiles) showed the largest variation in the general shape of hard and soft tissue, followed by the anteroposterior dimensions (mild to severe skeletal II patterns). Variations of lip shape (long to short), lip protuberance (everted to inverted), and nasolabial angle (obtuse to acute) were present. Orthodontic treatment affected the shape of the hard and soft tissue significantly (p < 0.0001). T2 showed significant uprighting of upper incisors (17.5o) and lower incisors (3.7o), improved NLA (8o), an increase in upper lip thickness (1.5 mm), and a reduction in lower lip thickness (0.7 mm) (p < 0.05). Conclusion Vertical and anteroposterior shape variations were found. Orthodontic treatment had an impact on both hard and soft tissue shapes. Hence, understanding both the hard and soft tissue shape variations and the orthodontic treatment changes is crucial for an accurate diagnosis and treatment plan to achieve a successful outcome and excellent patient satisfaction.